Pengembangan Bahan Ajar Berbasis Cerita Fabel Pada Materi Aturan Norma Yang Berlaku Dalam Kehidupan Sehari-hari Pembelajaran di Kelas IV SDN Margasari - Ismawati, Fitri; Jamaludin, Ujang; Taufik, Muhammad (Universitas Muhammadiyah Magelang, 2025)
Learning activities cannot be separated from books as a teaching resource that is commonly used by teachers and students in particular so that books as media and learning resources can support the achievement of learning targets, especially in PPKn subjects. This research and development aims to determine the stages of development, feasibility and student responses to fable-based teaching materials on the material of rules and norms that apply in everyday life in learning in class IV SDN Margasari. This study uses the Borg and Gall method modified by Sugiono consisting of 6 steps, namely, problem analysis, data collection, product design, expert validation, product revision, and product trial. The data collection techniques for this study are interviews, observations, questionnaires and documentation. The subjects of this study were 28 fourth grade students of SDN Margasari. The results of the study showed that the average validation value from the expert team was 83% in the